Malaysia's Digital Economy : A New Driver of Development - World Bank Group (World Bank, Washington, DC, 2018)
This report examines three interrelated issues — digital connectivity, digital entrepreneurship, and taxation of digital platforms — that are closely aligned with Malaysia’s goal of becoming the e-commerce hub of the region. By leveraging the internet, smartphones, Big Data, the internet of things, artificial intelligence, and other technologies, Malaysia can increase productivity, spur innovation, and improve livelihoods. Digital technologies can drive economic growth in Malaysia through three channels. First, they can promote inclusion by enabling existing firms and entrepreneurs to serve markets that are currently underserved. Second, they can lower costs and increase efficiency for existing firms and entrepreneurs to make them more competitive. And third, they can encourage innovation and scale economies, allowing entirely new forms of business and entrepreneurship to emerge.